Temporal analysis of vaginal proteome reveals developmental changes in lower reproductive tract of gilts across the first two weeks postnatal - Harlow, KaLynn (Sci Rep, 2019)
In swine the upper reproductive tract undergoes early postnatal development, however little is known about the lower reproductive tract. Our objective was to measure cytology and proteome of vaginal swab samples taken on postnatal day (PND) 2 and 16 in gilts to determine if temporal changes occurred in cell and protein profiles during the first two weeks after birth. The posterior vagina was swabbed using a cytology brush on PND 0, 2 and 16 and slides were prepared. The proportion of anuclear and superficial cells increased and parabasal decreased (P < 0.05) from PND 0 to 16. Proteins isolated from vaginal swabs taken on PND 2 and 16 from six gilts across three litters were measured using LC-MS/MS. Over 1500 proteins were identified, with 881 differentially expressed (P-adj < 0.05) between PND 2 and 16. One-third of proteins upregulated between days were categorized as secreted, including lipocalins. Categories enriched by downregulated proteins included cell-cell adherens junction, translation and ER to Golgi vesicle-mediated transport, and reflected increased cornification of stratified epithelium and thus mirrored changes in cytology. Changes in cytology and proteome over the first two weeks after birth support that the porcine vagina continues to develop postnatal.